The effects of death anxiety on diet-fluid restriction non-adherence in hemodialysis patients - Turan, Guelcan Bahcecioglu; Ozer, Zulfunaz; Basak, Seda (Wiley, 2025)
IntroductionThe study was performed to examine the effects of death anxiety on diet-fluid restriction non-adherence in hemodialysis patients.MethodsThis descriptive, cross-sectional, and correlational study was performed with 118 hemodialysis patients who received treatment in the dialysis unit of a university hospital and a state hospital in Elaz & imath;& gbreve;, eastern Turkey. The study data were obtained with the Descriptive Data Form, Death Anxiety Scale, and Dietary and Fluid Restriction Non-Adherence Scale.FindingsThe average Death Anxiety Scale total score of the patients was 10.00 +/- 4.75. The Duration of non-adherence with diet mean score was 1.66 +/- 1.70, Degree of non-adherence with diet mean score was 1.24 +/- 1.19, Duration of non-adherence with fluid restriction mean score was 1.61 +/- 1.71, and Degree of non-adherence with fluid restriction mean score was 1.16 +/- 1.13. The independent variable Death Anxiety Scale significantly and negatively affected the dependent variable Duration of non-adherence with diet, Degree of non-adherence with diet, Duration of non-adherence with fluid restriction, and Degree of non-adherence with fluid restriction.DiscussionHemodialysis patients face serious death anxiety, their degree of non-adherence with diet-fluid restriction was low as death anxiety scores increased, and the degree of non-adherence with diet-fluid restriction decreased.
Keywords: death anxiety; hemodialysis patient; non-adherence with diet-fluid restriction